Improvement of Web-Based Patient Receivables Collection Information System at RSU Imelda - Lumbanbatu, Maristella J. (SEAN Institute, 2022)
The use of Information Technology (IT) now plays an essential role in the success of an organization's business. By storing information digitally, a company is able to access customer information and process its orders quickly. A doctor can immediately give action to patients after accessing complete patient medical records without having to unpack paper files stored in the hospital. This can be done thanks to the computer-based system used to process information, specifically the Management Information System (SIM). Imelda Perkaja Indonesia Hospital is a Type B referral hospital in Medan City, North Sumatra, where there are often patients who are unable to make payments after treatment both outpatient and inpatient, especially patients pay themselves, where every patient who is unable to pay, this author makes a patient receivables payment system. Management utilizes PHP programming language and MySql database where patient receivables data has been recorded by the computer and the validation process of patient receivables payments, as for several features in this patient receivables information system where patient data input and patient receivables recording can be done.